Composite resin composition with excellent weather resistance and thermal radiation properties, composite resin-coated steel sheet, and manufacturing method thereof

A composite resin-coated steel sheet with heat-radiating and weather-resistant coatings addresses the inefficiencies of solar modules by enhancing heat dissipation and weather resistance, improving power generation efficiency and durability.

JP7612004B2Active Publication Date: 2025-01-10POHANG IRON & STEEL CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023515739
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-09-28
Filing Date
2021-09-24
Publication Date
2025-01-10
Estimated Expiration
2041-09-24

AI Technical Summary

Technical Problem

Solar modules face issues with high installation costs due to their weight and insufficient environmental safety, and their power generation efficiency decreases significantly with rising temperatures, necessitating inefficient and costly heat dissipation methods.

Method used

A composite resin composition comprising modified polyester resin, curing agents, pigments, and catalysts is applied to both sides of a plated steel sheet, forming a heat-radiating and weather-resistant coating layer to enhance heat dissipation and weather resistance, respectively.

Benefits of technology

The composite resin-coated steel sheet effectively radiates heat, lowering surface temperatures and improving power generation efficiency while providing excellent weather resistance, suitable for solar cell applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007612004000004
    Figure 0007612004000004
  • Figure 0007612004000005
    Figure 0007612004000005
  • Figure 0007612004000006
    Figure 0007612004000006
Patent Text Reader

Abstract

The present invention relates to a composite resin composition having excellent weather resistance and thermal radiation properties, which is used to provide a material suitable for use in photovoltaic cells, a composite resin-coated steel sheet obtained from the composite resin composition, and a method for producing the same.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composite resin composition having excellent weather resistance and thermal radiation properties, a composite resin-coated steel sheet, and a method for producing the same. [Background technology]

[0002] Recently, solar cells that utilize sunlight have been attracting attention as an environmentally friendly energy source that can overcome environmental problems such as CO2 emissions and fine dust generation caused by the excessive use of fossil fuels. Solar cells are a technology that converts light energy into electrical energy through the photoelectric effect.

[0003] The most commonly used photovoltaic cells in solar technology are silicon-based photovoltaic cells, which are available in crystalline and amorphous types. Recently, with the development of thin-film technology, CIGS (CuInGaSe) photovoltaic cell technology has made great strides.

[0004] In particular, there has been great progress in the technology for manufacturing integrated solar modules that use CIGS thin-film solar cells and are intended for application to the roofs and walls of buildings.

[0005] However, while solar module manufacturing technology has great advantages as an environmentally friendly energy technology, it also has two problems that need to be overcome.

[0006] First, there is a structural problem. Crystalline silicon solar modules are composed of reinforced glass on top, encapsulant, solar cell, encapsulant, and backsheet on the bottom, in that order, which not only makes the solar module heavy, but also makes it less safe for the environment. This means that a sturdy structure must be installed on top of the building, and the modules must then be installed on top of it, which increases the installation costs.

[0007] Secondly, there is the issue of heat. As solar cells generate electricity using the properties of semiconductors, they are not only highly dependent on the amount of sunlight, but also suffer from the problem that their power generation efficiency drops significantly when summer temperatures rise. Generally, when the surface temperature of the module reaches 45°C or higher, the power generation efficiency drops sharply to -0.45% / °C, but if the surface temperature of the solar module remains at a high temperature of around 60-80°C during the summer when the atmospheric temperature is at its highest, the average power generation efficiency of sunlight drops from 20% to 12%.

[0008] In order to solve these problems, methods have been applied such as attaching a heat dissipation sheet or a heat dissipation fin, or installing an additional cooling device such as a heat dissipation fan, but these are undesirable in terms of efficiency and cost.

[0009] Furthermore, because roofs, walls, and other buildings to which solar modules are applied are exposed to the outdoors, the backsheet must be weather resistant to ensure stable use in such environments for more than 20 years. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] Korean Patent Publication No. 10-1487962 Summary of the Invention [Problem to be solved by the invention]

[0011] One aspect of the present invention is to provide a composite resin composition having excellent weather resistance and thermal radiation properties, which is suitable for use in solar cells, and to provide a composite resin-coated steel sheet obtained from the composition and a method for producing the same.

[0012] The object of the present invention is not limited to the above. The object of the present invention can be understood from the entire contents of this specification, and a person having ordinary skill in the art to which the present invention pertains will have no difficulty in understanding the additional object of the present invention. [Means for solving the problem]

[0013] One aspect of the present invention provides a composite resin composition that contains, relative to 100 parts by weight of a total, (a) 20 to 60 parts by weight of a base resin made of a modified polyester resin, (b) 3 to 20 parts by weight of a curing agent, (c) pigments: 1 to 20 parts by weight of an anti-rust pigment and 1 to 20 parts by weight of a thermally conductive pigment, (d) catalyst agents: 0.05 to 3.0 parts by weight of an acid catalyst and 0.05 to 5.0 parts by weight of an amine catalyst, (e) 0.05 to 5.0 parts by weight of a wax, and (d) the balance being a solvent, and that forms a wrinkle pattern or an uneven structure on the surface of a dried coating film and has excellent weather resistance and thermal radiation properties.

[0014] Another aspect of the present invention provides a composite resin-coated steel sheet comprising: a plated steel sheet; a heat-dissipating coating layer on a first surface of the plated steel sheet; and a weather-resistant coating layer on a second surface of the plated steel sheet, wherein the heat-dissipating coating layer is formed from the above-mentioned composition to form a wrinkle pattern or an uneven structure on the surface, and the weather-resistant coating layer is formed from a composition obtained by excluding a part of a catalyst agent and a wax component from the above-mentioned composition.

[0015] Yet another aspect of the present invention provides a method for manufacturing a composite resin-coated steel sheet, the method including the steps of: a) preparing a plated steel sheet; b) applying the above-described composition to a first surface of the plated steel sheet and applying a composition, in which some of the catalyst and wax components are excluded from the above-described composition, to a second surface of the plated steel sheet; and c) drying the compositions applied to the first and second surfaces at a PMT (Peak Metal Temperature) of 180 to 260°C, wherein the second surface is a surface to be bonded to a solar module. Effect of the Invention

[0016] The composite resin-coated steel sheet obtained using the composite resin composition according to the present invention has excellent weather resistance and thermal radiation characteristics, and is therefore suitable as a roofing material for solar cells, etc., and can thereby obtain the effect of improving the power generation efficiency of solar cells. [Brief description of the drawings]

[0017] [Figure 1] 1 is a side cross-sectional view of a composite resin-coated steel sheet according to an embodiment of the present invention. [Diagram 2] 1 shows the results of microscopic observation of the coating layer (thermal radiation coating layer) of an inventive steel 10 (a) according to one embodiment of the present invention and a comparative steel 1 (b). [Diagram 3] 1 shows the results of measuring the surface roughness of the coating layer of an invention steel 10 according to an embodiment of the present invention and a comparative steel 1. [Figure 4] 1 shows a heat radiation temperature measuring device according to an embodiment of the present invention. [Diagram 5] The results of measuring the heat dissipation characteristics of an inventive steel 10 according to an embodiment of the present invention, a comparative steel 1, and a control steel are shown. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The inventors of the present invention have conducted intensive research to solve the problems of existing solar integrated module manufacturing techniques. In particular, the inventors have confirmed that a coated steel sheet suitable for a building such as a roof or wall to which a solar module is applied can be provided by utilizing a plated steel sheet known to have excellent corrosion resistance and coating it with a composition having excellent weather resistance and thermal radiation properties, thereby completing the present invention.

[0019] The present invention will be described in detail below.

[0020] First, a composite resin composition having excellent weather resistance and thermal radiation properties according to one aspect of the present invention will be specifically described.

[0021] The composite resin composition according to the present invention may be composed of a base resin, a curing agent, a pigment, a catalyst, and a remaining solvent, and is characterized by being composed of a composition further containing a wax component and a composition excluding a part of the catalyst and the wax component. In this specification, it is made clear that the composite resin composition further containing the wax component can be represented as composition 1, and the other composite resin composition can be represented as composition 2.

[0022] As will be described in detail later, the compositions 1 and 2 of the present invention can form respective coating layers on the surface of a substrate to which the compositions can be applied, and the coating layers can have surface shapes that are distinct from each other. In other words, the compositions 1 and 2 can be applied to different surfaces of the substrate to form dry coating films. As will be described in more detail later, in the present invention, the substrate can be a metal material, for example, a plated steel sheet.

[0023] First, the above-mentioned composition will be specifically described.

[0024] The composition 1 can contain (a) a base resin made of a modified polyester resin, (b) a curing agent, (c) a pigment made of an anti-rust pigment and a thermally conductive pigment, (d) a catalyst agent made of an acid catalyst and an amine catalyst, and (e) a wax. The composition 1 can form a certain pattern such as a wrinkle pattern or an uneven structure on the surface of a dried coating film.

[0025] The preferred content of each component will be explained in detail below, and it will be made clear that the content of each component is based on 100 parts by weight of the total.

[0026] The base resin made of the modified polyester resin (a) may be contained in an amount of 20 to 60 parts by weight per 100 parts by weight of the total.

[0027] The polyester resin is a main component for forming a coating film (coating layer), and in the present invention, a modified polyester resin having an average molecular weight (Mw) of 5,000 to 50,000 can be used. If the molecular weight is less than 5,000, the chemical resistance and processability of the coating film become insufficient. On the other hand, if it exceeds 50,000, there is a problem that the storage stability and workability of the solution are poor. More preferably, the average molecular weight may be 10,000 to 40,000.

[0028] Such modified polyester resins may have hydroxyl groups (OH groups, hydroxyl groups). Preferably, the resin may have a hydroxyl number of 20 to 60, more preferably 30 to 50. If the hydroxyl number is less than 20, the crosslinking property of the coating film may decrease. On the other hand, if it exceeds 60, the chemical resistance of the coating film may decrease.

[0029] The modified polyester resin may have an acid value of 1 to 20 mgKOH / g, preferably 5 to 15 mgKOH / g. If the acid value exceeds 20 mgKOH / g, the chemical resistance of the coating film decreases. On the other hand, if the acid value is less than 1 mgKOH / g, the crosslinking property of the coating film decreases.

[0030] If the content of the modified polyester resin in the composition provided by the present invention is less than 20 parts by weight or more than 60 parts by weight, the drying property may be poor when the coating film is cured, or the crosslinking property or chemical resistance may be reduced.

[0031] In the present invention, the modified polyester resin is a binder resin that forms a fine pattern, for example a wrinkled pattern or an uneven structure, on the surface of the coating film when cured, and has excellent processability and weather resistance.

[0032] The (b) hardener may be included in an amount of 3 to 20 parts by weight, more preferably 5 to 15 parts by weight, based on 100 parts by weight of the total.

[0033] The above curing agent can be added in order to form a dense cured film from the viewpoint of the physical properties of the coating film, and the above curing agent is preferably an amine-based curing agent.

[0034] More preferably, the amine-based hardener may be a melamine-based hardener. Although not limited thereto, the melamine-based hardener may be one or more selected from hexa(N-butoxy)methylmelamine, hexa(iso-butoxy)methylmelamine, hexa(N-propyl)methylmelamine, hexa(iso-propyl)methylmelamine, hexaethoxymethylmelamine, and hexamethoxymethylmelamine. That is, the melamine-based hardener may be used as a single compound or as a mixture of two or more compounds.

[0035] In the composition provided by the present invention, if the content of the amine-based curing agent is less than 3 parts by weight or more than 20 parts by weight, it may be disadvantageous in forming a dense cured coating.

[0036] When a coating film (coating layer) is formed using the composition provided by the present invention, a pigment may be contained in the composition in order to improve the corrosion resistance and other properties of the coating film.

[0037] In the present invention, the pigment (c) may be a mixture of an anti-rust pigment and a thermally conductive pigment, and each pigment may be contained in an amount of 1 to 20 parts by weight, more preferably 5 to 15 parts by weight, per 100 parts by weight of the total.

[0038] The rust-preventive pigment is preferably a silicate compound, and may be, for example, one or more of lithium polysilicate, sodium polysilicate, potassium polysilicate, and colloidal silica, but is not limited thereto.

[0039] The thermally conductive pigment is preferably a component capable of realizing black color when a coating film is formed, and is preferably an organic-inorganic thermally conductive pigment in the present invention. As an example, the organic-inorganic thermally conductive pigment may be one or more of carbon black, carbon nanotubes, graphite, and graphene, but is not limited thereto.

[0040] If the content of the anti-rust pigment in the composition provided by the present invention is less than 1 part by weight, the anti-corrosion effect is insufficient, and if it exceeds 20 parts by weight, the corrosion resistance is improved, but the coating film becomes rough and the processability is poor. If the content of the thermally conductive pigment in the composition is less than 1 part by weight, the hiding rate and heat radiation properties of the material formed by the coating film may be low. On the other hand, if the content exceeds 20 parts by weight, the viscosity of the applied solution becomes high, the workability is reduced, and it is difficult to obtain a beautiful surface appearance.

[0041] When carbon black is used as the thermally conductive pigment, from the viewpoint of dispersibility, the average particle size is preferably 10 to 100 nm, and more preferably 10 to 30 nm.

[0042] When graphite is used as the thermally conductive pigment, the average particle size is preferably 3 to 30 μm, more preferably 5 to 20 μm. The graphite may have various shapes such as granular, plate-like, blocky, flake-like, etc., and any of these shapes can be used without any problem. However, in order to provide good thermal conductivity to the coating film produced, the graphite is preferably in the flake shape.

[0043] Meanwhile, when a certain pattern is formed on the surface of a coating film by the composition provided by the present invention, the more continuously the pigment particles are arranged inside the pattern, the more the hardness of the coating film is increased and the more the texture and design are improved.To this end, it is preferable that the average particle size of the pigment particles is in the range of 20±5 μm based on the thickness of the dried coating film of the composition.

[0044] In order to promote the curing reaction between the binder resin, which is the main component of the composition provided by the present invention, and the curing agent, and thereby to improve the hardness of the coating film, a catalyst may be included as a curing reaction accelerator.

[0045] In the present invention, the (d) catalyst agent may contain a mixture of an acid catalyst and an amine catalyst, and may contain 0.05 to 3.0 parts by weight and 0.05 to 5.0 parts by weight, respectively, relative to 100 parts by weight of the total.

[0046] The acid catalyst may be a substance blocked with an organic chain that can be dissociated by heat, and preferably, a sulfonic acid may be used, but it is not limited thereto.

[0047] Examples of the sulfonic acid include p-toluenesulfonic acid, dodecylbenzenedisulfonic acid, dinonyltoluenedisulfonic acid, dinonylnaphthalenesulfonic acid, and mixtures thereof. In the case of the mixture, two or more compounds may be mixed. In addition, an epoxy resin-based or amine-based compound may be used as the blocking material. As one example, dinonylsulfonic acid shielded with epoxy resin (a material with a dissociation temperature of 160°C or more and an activity of 30% from King Co., USA) may be used.

[0048] The amine catalyst may be classified into primary amine (NH2-R1), secondary amine (NH-R1, -R2), and tertiary amine (N-R1, -R2, -R3), where the substituted hydrocarbon (R1, R2, R3) may be an aliphatic or aromatic chain. The amine catalyst may be, but is not limited to, diethylamine, diisopropylamine, diisopropanolamine, di-n-propylamine, di-n-butylamine, diisobutylamine, di-secondary-butylamine, diallylamine, diamylamine, N-ethyl-1,2-dimethylpropylamine, N-methylhexylamine, di-n-octylamine, piperidine, 2-pipecoline, 3-pipecoline, 4-pipecoline, morpholine, or a mixture thereof.

[0049] Meanwhile, the composition provided by the present invention can form a certain pattern on the surface of the coating film, and in this case, the amine catalyst plays a major role. Specifically, after the composition is applied, a certain pattern can be formed on the surface due to the difference in curing speed between the inside and the surface of the coating film during a curing reaction at high temperature, and in order to advantageously obtain this, it is preferable to select and use the amine catalyst as a material having a higher volatility than the acid catalyst.

[0050] If the content of the acid catalyst in the composition provided by the present invention is less than 0.05 parts by weight, or if the content of the amine catalyst is less than 0.05 parts by weight, the curing temperature of the coating film becomes too high, and the physical properties of the coating film cannot be maintained. On the other hand, if the content of the acid catalyst exceeds 3.0 parts by weight, or if the content of the amine catalyst exceeds 5.0 parts by weight, curing occurs too quickly, or the stability of the solution over time becomes poor.

[0051] Generally, when a paint contains wax, it is used for the purpose of improving the friction characteristics of the coating film. However, in the present invention, it is significant to use wax for the purpose of forming a certain pattern when the coating film hardens after the solution is applied.

[0052] In the present invention, the wax (e) may be contained in an amount of 0.05 to 5.0 parts by weight, more preferably 0.1 to 3.0 parts by weight, based on 100 parts by weight of the total.

[0053] Specifically, the present invention preferably uses an insoluble wax that is difficult to dissolve in an organic solvent in order to form a pattern such as a wrinkled pattern or an uneven structure on the surface of a dried coating film obtained after coating and curing the composition. The insoluble wax exists in a solid state at room temperature and low temperature and is uniformly distributed in the paint, but as the wax melts upon curing at high temperature, a local difference in surface tension occurs on the surface of the coating film depending on the presence or absence of a wax component, which can be the starting point for the formation of a pattern such as wrinkles in the wax molecules.

[0054] The insoluble wax may be one or more of, but is not limited to, polyethylene, polypropylene, polyvinyl acetate, polystyrene, polystyrene-acrylonitrile, acrylic polymer, and polytetrafluoroethylene wax.

[0055] If the wax content in the composition provided by the present invention is less than 0.05 parts by weight, wrinkles or unevenness are formed widely and it is difficult to form them in a uniform pattern, whereas if the wax content exceeds 5.0 parts by weight, the wrinkles or unevenness are too narrow and it is not possible to obtain a uniform texture.

[0056] In the composition provided by the present invention, a solvent may be included as the balance other than the above-mentioned blended components for convenience of operation and adjustment of viscosity. As the solvent, toluene, xylene, isopropanol, solvent naphtha, cellosolve, cellosolve acetate, butyl cellosolve, etc. may be used, and these solvents may be used alone or in a mixture of two or more kinds.

[0057] The viscosity of the composition is adjusted according to the content of the solvent, and the amount of the solvent is not particularly limited, and the content can be adjusted according to a technique commonly used in this technical field. The content of the solvent can be adjusted in consideration of the adjustment of the coating amount (application amount) of the composition and adhesion, etc., and it is advantageous from the viewpoint of productivity to adjust the content of the solvent to an amount that gives a viscosity of about 20 to 200 seconds for the composition to be discharged from a DIN cup (DIN, 53211).

[0058] As described above, the present invention provides a composite resin composition (composition 1) containing all of the above-mentioned components, and a composite resin composition (composition 2) excluding some of the catalyst agent and wax component from the above components.

[0059] Specifically, the composition 2 may include (a) a base resin consisting of a modified polyester resin, (b) a curing agent, (c) a pigment consisting of an anti-rust pigment and a thermally conductive pigment, and (d) a catalyst consisting of an acid catalyst.

[0060] Since such composition 2 does not include an amine-based catalyst agent and a wax component that affect the surface shape of the dried coating film obtained after application and curing of the composition, the dried coating film formed by the composition 2 does not have a fixed pattern, i.e., has a flat surface shape.

[0061] The above components are as described above, so detailed description will be omitted. The content of each component is also as described above, and it is clear that the content of the components excluded from Composition 1 can be replaced with the remaining components.

[0062] Meanwhile, the composition may contain a solvent as the balance other than the above-mentioned components, and the solvent is as described above.

[0063] When the composite resin composition provided by the present invention, i.e., each of Composition 1 and Composition 2, is applied to a specific substrate to form a dry coating film, additives may be further included as necessary to further improve the physical properties of the substrate.

[0064] Specifically, regardless of the above Composition 1 and Composition 2, any composition may further contain one or more of a pigment aggregation inhibitor, a defoamer, and a leveling agent.

[0065] These optional additives are components generally known in the technical field of the present invention, and their blending ratios, etc. are not particularly limited. A person of ordinary skill in this technical field can use these additives by blending them appropriately as needed.

[0066] A composite resin-coated steel sheet having a given paint film layer (coating layer) formed by applying the above-mentioned composite resin composition according to another aspect of the present invention will be described in detail below.

[0067] The composite resin-coated steel sheet according to the present invention may be applied to a plated steel sheet as a substrate on which the above-mentioned composite resin compositions can be applied on different surfaces.

[0068] That is, each composite resin composition can be applied to both sides of the plated steel sheet, thereby resulting in one side (first side) having a heat-dissipating coating layer and the other side (second side) having a weather-resistant coating layer.

[0069] In the present invention, the heat-dissipating coating layer formed on the first side of the plated steel sheet can be formed from composition 1 containing a wax component among the above-mentioned composite resin compositions, and the weather-resistant coating layer formed on the second side can be formed from composition 2 excluding the above-mentioned wax component and some of the catalyst components.

[0070] The composite resin-coated steel sheet provided by the present invention can be applied to structures such as roofs or walls of solar cells. In particular, in the present invention, the weather-resistant coating layer on the second surface can be bonded to a solar module.

[0071] Therefore, in the plated steel sheet, the first surface corresponds to the lower surface and the second surface corresponds to the upper surface, and the second surface can be naturally exposed to the external environment.

[0072] As described above, the present invention provides an effect of effectively radiating heat from the solar cells and lowering the surface temperature by forming a heat-dissipating coating layer on the first surface of the plated steel sheet and a weather-resistant coating layer on the second surface. In addition, in the case of the surface on which the solar module is directly attached, it has an advantage of being excellent in weather resistance and can be used in an external environment for a long period of time.

[0073] The heat-dissipating coating layer and the weather-resistant coating layer may each have a thickness of 3 to 40 μm, more preferably 5 to 30 μm, based on the thickness of the dry coating.

[0074] If the thickness of each coating layer is less than 3 μm, the color, hiding power, processability and solvent resistance of the coating film formed from the composite resin composition are poor, whereas if the thickness exceeds 40 μm, there are problems such as an increase in production cost and a decrease in workability.

[0075] The plated steel sheet may be a galvanized steel sheet. Examples of the galvanized steel sheet include, but are not limited to, any one of hot-dip galvanized steel sheet (GI), alloyed hot-dip galvanized steel sheet (GA), electrogalvanized steel sheet (EG), alloyed aluminum-plated steel sheet (Al-Zn, Al-Zn-Si), and alloyed hot-dip galvanized steel sheet (Zn-Al-Mg).

[0076] As a more specific example, the aluminum alloyed plated steel sheet may have a plated layer composed of Al-55%Zn or Al-8%Zn-0.3%Si, and the galvannealed hot-dip plated steel sheet may be a ternary (Zn-xAl-yMg) plated steel sheet having a plated layer composed of Zn-(1.0-3.0%)Al-(1.0-5.0%)Mg, but is not limited thereto.

[0077] As yet another aspect of the present invention, a method for producing the above-mentioned composite resin-coated steel sheet will be described in detail.

[0078] To produce the composite resin-coated steel sheet of the present invention, a plated steel sheet can first be prepared.

[0079] The plated steel sheet may be a zinc-plated steel sheet, the types of which have been described above and will not be described here.

[0080] A composite resin composition can be applied to both sides of the plated steel sheet prepared as described above, and in this case, it is preferable to apply composition 1 containing a wax component to the lower side, which corresponds to the first side of the plated steel sheet, and composition 2, which excludes the wax component and a portion of the catalyst agent, to the second side, i.e., the upper side, of the plated steel sheet. Here, it is clear that the second side of the plated steel sheet is the surface that is bonded to the actual object to which the present invention is applied, i.e., the solar module.

[0081] When applying each of the composite resin compositions, any known method for applying a composition may be applied, for example, one of a bar coater, a roll coater, a slot-die coater, and a curtain coater.

[0082] The plated steel sheet having each side coated with the composite resin composition of the present invention as described above is baked and dried to produce the final composite resin-coated steel sheet.

[0083] In this case, the drying temperature can be in the range of 180 to 260°C based on the PMT (Peak Metal Temperature) of the plated steel sheet. If the baking temperature during the drying is less than 180°C based on the PMT, the reaction between the inorganic matter in the composition and the resin is insufficient, resulting in an insufficient coating layer. On the other hand, if the temperature exceeds 260°C, an over-curing reaction occurs, resulting in a problem of poor coating performance.

[0084] The applied composition may be dried by any method generally known in the art, including, but not limited to, a hot air heating method, an infrared heating method, or an induction heating method.

[0085] When the drying method is a hot air heating method, the applied composition can be dried by hot air treatment for 10 to 50 seconds at an atmospheric temperature of 200 to 340° C. When the method is an induction heating method, the composition can be dried for 5 to 20 seconds at a frequency range of 5 to 50 MHz and a power of 3 to 15 KW.

[0086] Meanwhile, the composite resin-coated steel sheet of the present invention may be subjected to an additional coating treatment in consideration of the workability, corrosion resistance, etc. of the plated steel sheet corresponding to the substrate, and an additional coating film may be formed thereon.

[0087] As one example, a pretreatment layer and an undercoat coating layer can be formed in sequence on one or both sides of the plated steel sheet, and in this case, it is also possible to form only the undercoat coating layer without forming the pretreatment layer.

[0088] The composite resin composition of the present invention can be applied onto such a pretreatment layer and / or undercoat coating layer to form the composite resin coating layer (preferably a heat dissipation coating layer and a weather-resistant coating layer) intended by the present invention. Such a coated steel sheet can have the effect of further improving processability.

[0089] The pretreatment layer and / or undercoat coating layer may be located between the plated steel sheet and the composite resin coating layer that is ultimately to be formed in the present invention, in which case the composite resin coating layer may be referred to as a topcoat coating.

[0090] FIG. 1 is a side cross-sectional view of a composite resin-coated steel sheet formed using the composite resin composition provided by the present invention, and the coating layer of the composition may have a black color.

[0091] As shown in (a) of Figure 1, a pretreatment layer and / or an undercoat coating layer further formed on the upper and lower surfaces of a plated steel sheet having zinc-based plating layers formed on both sides thereof can increase the adhesive strength between the steel sheet and a coating layer made of a composite resin composition, and can impart required physical properties to the steel sheet, such as workability, corrosion resistance, etc. The compositions for forming the pretreatment layer and undercoat coating layer are not particularly limited, and any coating known in this technical field as being applicable between a steel sheet and a composite resin coating layer may be used.

[0092] 1(b) shows a cross-sectional side view of a composite resin-coated steel sheet when one side of the sheet is bonded to a solar module, where the side bonded to the solar module is a flat weather-resistant coating layer, and the opposite side is a heat-dissipating coating layer having a certain pattern such as a wrinkled or uneven structure.

[0093] The present invention will be described in more detail below with reference to examples. However, the description of such examples is for illustrating the implementation of the present invention, and the present invention is not limited by the description of such examples. The scope of the present invention is determined by the matters described in the claims and matters that can be reasonably inferred therefrom. EXAMPLES

[0094] (Example) The composite resin composition was produced as follows.

[0095] First, as the base resin, 30-50 parts by weight of urethane-modified polyester resin (average molecular weight: 10000-30000, hydroxyl value 30, acid value 10mgKOH / g) was prepared for 100 parts by weight of the total composition, and 5-10 parts by weight of melamine-cured (Hexamethoxymethyl Melamine, HMMM) resin, 0.5-2.0 parts by weight of acid catalyst (Nacure 1419) blocked with epoxy resin, 0.5-3.0 parts by weight of amine catalyst (dibutylamine), 5-10 parts by weight of rust-preventive pigment (spherical silica, average particle size 20μm) and thermally conductive pigment (graphite, average particle size 20μm) were added, and then dispersed. At this time, the blending of each component was performed as shown in Table 1 below.

[0096] Meanwhile, another composite resin composition for forming a coating layer to be bonded to a solar module was prepared by similarly blending the above-mentioned components except for the amine catalyst and wax, and replenishing the contents of the excluded components with a solvent.

[0097] As the solvent for each of the above compositions, an organic solvent (ketone and ester-based petrochemical solvent) was used.

[0098] [Table 1] (In Table 1, each component is based on parts by weight.)

[0099] Composite resin-coated steel sheets having coating layers formed using the respective solutions prepared as described above were produced as follows.

[0100] First, the plated steel sheets (one-sided plating amount 60 g / m2) shown in Table 2 were 2 After preparing the plated steel sheet, a pretreatment layer and an undercoat layer were formed in sequence on both sides of the plated steel sheet. At this time, the pretreatment solution was added to the plated steel sheet so that the dry coating amount was 100±50 mg / m 2The substrate was roll-coated so that the thickness of the dried coating film was 5±2 μm, and then the substrate was dried by baking at PMT=210°C and cooled to form an undercoat coating layer.

[0101] The upper and lower surfaces of the plated steel sheet on which the pretreatment layer and the undercoat coating layer were formed in sequence as described above were divided, and a composition capable of forming a weather-resistant coating layer, i.e., a composition solution excluding amine-based catalysts and wax components, was applied to the upper surface, and a composition solution capable of forming a heat-dissipating coating layer was applied to the lower surface. At this time, each composition solution was roll-coated to a dry coating thickness of 10 to 25 μm, and then cured and dried at PMT=232°C and cooled to produce a composite resin-coated steel sheet with coating layers formed on both sides of the plated steel sheet.

[0102] The composite resin-coated steel sheets manufactured as described above were subjected to a quality evaluation, and the results are shown in Tables 2 and 3.

[0103] First, the thickness of the coating layer formed using the above-mentioned composition solution was measured with a non-destructive portable coating thickness gauge.

[0104] The pencil hardness was evaluated by drawing a 10 cm line at an angle of 45° with a Mitsubishi pencil (HB to 4H) under a load of 1000±10 g, and then counting whether scratches were generated.

[0105] The corrosion resistance was evaluated using the Cyclic Corrosion Test (CCT). The specimens were sprayed with salt water (concentration 5%, 1kg / cm at 35℃) for 5 hours under a relative humidity of 95%. 2 After the coating was dried at 70°C and 30% relative humidity for 2 hours, the coating was further treated at 50°C and 95% relative humidity for 3 hours. This cycle was repeated 100 times, and the surface area of ​​red rust on the surface of the coated steel sheet was evaluated.

[0106] The evaluation criteria were as follows: corroded area 0%: ◎; corroded area 5% or less: ○; corroded area over 5% to 30%: △; corroded area over 30%: ×.

[0107] The workability was evaluated by bending process, in which the coated steel sheet was placed in a vice, bent 180° with a pressure of 1 kgf, and then tightened until it became flat. Scotch tape was then applied to the surface of the bent coating, and the coating was peeled off to evaluate whether cracks occurred on the surface where the tape was peeled off and whether the coating peeled off.

[0108] The evaluation criteria were as follows: ⊚: no cracks or peeling of the coating film; ◯: no fine cracks in the coating film or peeling; Δ: severe cracks and no peeling; and ×: severe cracks and peeling of the coating film.

[0109] The surface roughness was measured using a three-dimensional roughness meter (Leica, DCM8). The evaluation criteria are as follows: 10 μm or more: ◎, 7 μm or more to less than 10 μm: ○, 5 μm or more to less than 7 μm: △, and less than 5 μm: ×, depending on the measured roughness value.

[0110] Acid resistance was evaluated by applying a 5% hydrochloric acid solution to the coating, covering the surface and shielding the periphery with Vaseline, and then leaving it at 25° C. for 24 hours before evaluating the condition of the coating.

[0111] The evaluation criteria were 5, with no traces at all and 1, with the entire surface peeling off, and the degree of peeling was rated as 1, 2, 3, 4, or 5.

[0112] The alkali resistance was evaluated by applying a 5% sodium hydroxide solution to the coating, covering the surface and shielding the periphery with Vaseline, and then leaving it at 25°C for 24 hours before evaluating the condition of the coating.

[0113] The evaluation criteria were 5, with no traces at all and 1, with the degree of peeling being rated as 1, 2, 3, 4, or 5.

[0114] Weather resistance was measured using a QUV-se device from Q-PANEL, USA. The value measured by adjusting the UV wavelength to type A (340 nm) was indicated as QUV-A, and the value measured by adjusting the UV wavelength to type B (313 nm) was indicated as QUV-B. In this case, for type A, UV was irradiated at 60°C for 8 hours as one cycle, and then maintained at 50°C for 4 hours for 1000 hours, and the maintenance rate was evaluated by comparing it with the initial gloss of the coating. For type B, UV was irradiated under the same conditions, and the temperature during maintenance was set to 40°C.

[0115] The evaluation criteria were as follows: ⊚: gloss level maintained at 90% or more relative to the initial gloss level; ◯: gloss level maintained at 85% or more but less than 90%; △: gloss level maintained at 80% or more but less than 85%; and ×: gloss level maintained less than 80%.

[0116] Thermal diffusivity and thermal conductivity were measured by the laser flash method (NETZSCH LFA 457) according to the KS L 1604:2017 test method.

[0117] The thermal emissivity was measured using an FT-IR spectrometer (DIMAC M4500) according to the KS L 2514:2011 test method.

[0118] Heat dissipation was evaluated and measured by creating a test device simulating a solar module, as shown in Figure 4. The test device was made of styrofoam (a) (insulation material) with a thickness of 26 mm and dimensions of 340 x 265 x 195 mm, and the inside was covered with aluminum foil (b). An infrared lamp (c) was installed in the center of the bottom of the test device, and a temperature gauge (d) was installed so that it was located in the center between the infrared lamp and the top end of the test device.

[0119] The coated steel sheet to be measured was placed on top of the open test equipment, and the temperature inside the box (A) and the change in surface temperature were measured after attaching thermocouples to both sides (B, C) of the steel sheet. The coated steel sheet sample (e) was prepared by cutting it to a size of 150cm wide x 150cm long, and attached to the top of the opening so that it was 50mm (α) away from the infrared lamp of the measurement equipment and sealed. The heat dissipation temperature was calculated after 60 minutes had passed since the measurement, as the temperature difference (heat dissipation temperature (ΔT) = (temperature of the measured test piece (coated steel sheet)) - (temperature of the uncoated alloy-plated steel sheet) of the coated steel sheet relative to the alloy-plated steel sheet simulating the solar module.

[0120] Here, the alloy-plated steel sheet for comparison with the coated steel sheet corresponds to the "comparison steel" in Tables 2 and 3, and is a Zn-1.5%Al-1.5%Mg plated steel sheet in which only pretreatment has been applied on the plating layer, and which is an alloyed hot-dip plated steel sheet on which neither an undercoat coating layer nor a composite resin coating layer is formed.

[0121] [Table 2] (The physical properties shown in Table 2 are the results of measurements on the heat-dissipating coating layer.)

[0122] [Table 3] (In Table 3, the weather resistance is the measurement result for the heat-dissipating coating layer, and the heat resistance properties are the measurement results for the material itself on which the heat-dissipating coating layer and the weather-resistant coating layer are formed.)

[0123] As shown in Tables 1 to 3, it can be seen that the composite resin-coated steel sheets (Invention Steels 1 to 28) in which a heat-dissipating coating layer is formed on one side of a plated steel sheet and a weather-resistant coating layer is formed on the other side using the composite resin composition provided by the present invention not only have excellent weather resistance but also excellent heat radiation properties.

[0124] In particular, the composite resin-coated steel sheet of the present invention has an advantage that the surface on which the weather-resistant coating layer is formed is joined to a solar module, while the opposite surface is formed with a heat-dissipating coating layer, which effectively radiates heat from the module surface to lower the surface temperature and has excellent weather resistance, making it suitable for use as a roofing material or wall material integrated into a building.

[0125] On the other hand, the coated steel sheets (comparative steels 1 to 4) manufactured using compositions other than those proposed in the present invention exhibited inferior thermal emissivity and significantly lower heat dissipation temperatures than the inventive steels.

[0126] FIG. 2 shows photographs of the coating layers of the inventive steel 10 and the comparative steel 1, particularly the surfaces and cross sections of the heat-dissipating coating layers, measured with a microscope (optical microscope, scanning electron microscope (SEM)).

[0127] As shown in FIG. 2, in the case of the inventive steel 10, it can be seen that a consistent wrinkle pattern was formed on the surface of the thermally conductive coating layer, whereas in the case of the comparative steel 1, no such pattern was observed.

[0128] In the photographs showing the cross sections of the above coating layers, the "arrow on the left" points to the primer coating layer, and the "arrows in the center and on the right" point to the thermally conductive coating layer (thermal-conductive coating layer).

[0129] 3 is a graph showing the measurement of the surface roughness of the inventive steel 10 and the comparative steel 1. As shown in FIG. 3, it can be seen that the surface roughness of the comparative steel 1 is much lower than that of the inventive steel 10.

[0130] Figure 5 is a graph showing the temperature change over time during the evaluation of heat dissipation. At this time, the invention steel 10, the comparative steel 1, and the control steel were compared with a reference material corresponding to an untreated test piece (a pure water-plated steel sheet that was not treated at all up to the pretreatment or undercoat coating).

[0131] As shown in Figure 5, the comparative steel, which does not have any coating layer made of the composition according to the present invention, has a very small heat dissipation effect even after time has passed. In the case of Comparative Steel 1, although a heat dissipation effect can be confirmed, it is clear that the effect is not as good as that of Example 10, which corresponds to the present invention.

Claims

1. For a total of 100 parts by weight, (a) 20 to 60 parts by weight of a base resin made of a modified polyester resin; (b) 3 to 20 parts by weight of a curing agent, (c) Pigments: 1 to 20 parts by weight of an anti-rust pigment and 1 to 20 parts by weight of a thermally conductive pigment; (d) Catalyst agent: 0.05 to 3.0 parts by weight of an acid catalyst and 0.05 to 5.0 parts by weight of an amine catalyst; (e) 0.05 to 5.0 parts by weight of an insoluble wax, and (f) remaining solvent; A composite resin composition that forms a wrinkle pattern or uneven structure on the surface of a dried coating film and has excellent weather resistance and heat radiation properties.

2. 2. The composite resin composition according to claim 1, wherein the modified polyester resin has an average molecular weight (Mw) of 5,000 to 50,000.

3. 2. The composite resin composition according to claim 1, wherein the modified polyester resin has 20 to 60 hydroxyl (OH) groups and an acid value of 1 to 20 mgKOH / g.

4. The curing agent is The composite resin composition according to claim 1, wherein the melamine-based curing agent is one or more selected from the group consisting of hexa(N-butoxy)methylmelamine, hexa(iso-butoxy)methylmelamine, hexa(N-propyl)methylmelamine, hexa(iso-propyl)methylmelamine, hexaethoxymethylmelamine, and hexamethoxymethylmelamine.

5. The rust-preventive pigment is a silicate compound, and is at least one of lithium polysilicate, sodium polysilicate, potassium polysilicate, and colloidal silica; 2. The composite resin composition according to claim 1, wherein the thermally conductive pigment is a black organic-inorganic pigment, and is at least one of carbon black, carbon nanotubes, graphite, and graphene.

6. The composite resin composition according to claim 1, wherein the acid catalyst is a sulfonic acid blocked with an organic chain, and is p-toluenesulfonic acid, dodecylbenzenedisulfonic acid, dinonyltoluenedisulfonic acid, dinonylnaphthalenesulfonic acid, or a mixture thereof.

7. 7. The composite resin composition according to claim 6, wherein the blocking is performed using an epoxy resin or an amine compound.

8. The amine catalyst is a primary amine (NH 2 -R 1 ), secondary amine (NH-R 1 , -R 2 ), tertiary amine (N-R 1 , -R 2 , -R 3 ) and substituted hydrocarbons (R 1 , R 2 , R 3 2. The composite resin composition according to claim 1, wherein the alkyl group is an aliphatic or aromatic chain.

9. The composite resin composition according to claim 8, wherein the amine catalyst is diethylamine, diisopropylamine, diisopropanolamine, di-n-propylamine, di-n-butylamine, diisobutylamine, di-sec-butylamine, diallylamine, diamylamine, N-ethyl-1,2-dimethylpropylamine, N-methylhexylamine, di-n-octylamine, piperidine, 2-pipecoline pipecoline, 3-pipecoline pipecoline, 4-pipecoline pipecoline, morpholine, or a mixture thereof.

10. The insoluble wax is 2. The composite resin composition according to claim 1, which is one or more of polyethylene, polypropylene, polyvinyl acetate, polystyrene, polystyrene-acrylonitrile, acrylic polymer, and polytetrafluoroethylene wax.

11. The composite resin composition according to claim 1 , further comprising at least one of a pigment aggregation inhibitor, a defoamer, and a leveling agent.

12. Galvanized steel sheet; a heat-dissipating coating layer on a first surface of the plated steel sheet; and The second surface of the plated steel sheet includes a weather-resistant coating layer; 2. A composite resin-coated steel sheet, comprising: the heat-dissipating coating layer formed from the composition according to claim 1, and having a wrinkle pattern or an uneven structure formed on the surface; and the weather-resistant coating layer formed from the composition according to claim 1, which does not contain the amine-based catalyst and the insoluble wax.

13. The composite resin-coated steel sheet according to claim 12 , wherein the weather-resistant coating layer on the second surface is a surface that is bonded to a solar module.

14. The composite resin-coated steel sheet according to claim 12, wherein the heat-dissipating coating layer and the weather-resistant coating layer each have a dry coating thickness of 3 to 40 μm.

15. The plated steel sheet is a zinc-plated steel sheet, The composite resin-coated steel sheet according to claim 12, wherein the galvanized steel sheet is any one of a hot-dip galvanized steel sheet (GI), a galvannealed steel sheet (GA), an electrogalvanized steel sheet (EG), an aluminum alloyed plated steel sheet (Al-Zn, Al-Zn-Si), and a galvannealed steel sheet (Zn-Al-Mg).

16. a) preparing a plated steel sheet; b) applying the composition according to claim 1 to a first surface of the plated steel sheet, and applying the composition according to claim 1, which does not include the amine-based catalyst and the insoluble wax, to a second surface of the plated steel sheet; and c) drying the composition applied to the first surface and the second surface at a PMT (Peak Metal Temperature) of 180 to 260° C.; The second surface is a surface to be joined to a solar module.

17. The method of claim 16, wherein the coating of the composition is performed using one of a bar coater, a roll coater, a slot-die coater, and a curtain coater.

18. The method of claim 16, wherein the step of drying the composition is performed by a hot air heating method, an infrared heating method, or an induction heating method.

Citation Information

Patent Citations

  • High quality textured composite resin composition and galvanized steel sheet coated with composite resin composition

    EP3444303A2

  • Coating composition and one-coat steel sheet

    JP1997111183A

  • Double-side coated base having improved contact abrasion property and manufacture thereof

    JP1998230566A

  • Excellent heat-dissipating black resin composition, method for treating galvanized steel sheets using the same, and galvanized steel sheets treated therewith

    JP2010514886A

  • Coated steel sheet, finished goods, and panel for thin-screen TV

    JP2013067159A